Effect of Vegetal Powders on Oviposition of Callosobruchus maculatus (Fabr.) (Coleoptera: Bruchidae) on Cowpea - Castro, Maria de Jesus P. de; Silva, Paulo Henrique; Santos, Jonas R.; Silva, José Algaci L. da (BioAssay, 2010)
ABSTRACT - Callosobruchus maculatus is one of the main pests of stored cowpea (Vigna unguiculata (L.) Walp.). This study investigated alternatives for the chemical control of these insects by determining, in lab conditions, the bioactivity of plant powders of Piper tuberculatum, Lippia sidoides, Sapindus saponaria and Melia azedarach on C. maculatus oviposition preference. A completely randomized design was performed with eight treatments and four repetitions (four treatments with 10% of one type of vegetal powder mixed to the grains and four control treatments with pure grains). Eighty adult insects were released and kept for 48 h in a eight-port olfactometre to choose among the treatments. The adults were then removed and the number of eggs laid on the grains recorded. The most efficient treatments were the powder of L. sidoides leaves, with 100% control, followed by P. tuberculatum fruits and S. saponaria leaves and seeds. The other treatments did not affect C. maculates ovoposition significantly.